Polymers with dispersing function, dispersants for oil well cement, and their manufacturing method and use
Patent Information
- Application Number
- JP2023534240
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-14
- Filing Date
- 2021-08-13
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2041-08-13
AI Technical Summary
【0053】 本発明の重合体は油井セメント分散剤として使用され、一般的な分散剤の20~120℃での強い水和抑制作用を解消し、カルボキシ基の含有量を減少させ、スルホン酸基を増加させることにより、水和抑制作用を低減させ、凝結遅延性を低下させ、また、長鎖シランがセメント及び水和生成物に化学結合を介して連結されるので、吸着性が向上し、スルホン酸と配合して分散性に影響を与えずにセメントの凝結遅延性を効果的に調整することができ、使用する際には、該分散剤は、セメントスラリーの流動性能の課題を解決するに加えて、スラリーの沈降安定性を改善させ、添加剤とよく適合しているとともに、マイクロシリカ、ラテックスなどの混和材に対して良好な適合性や分散性を持ち、中低温セメンチングのステップに適用でき、油井セメント分散剤の実用的なニーズを満たす。
Smart Images

Figure 0007634096000018 
Figure 0007634096000001 
Figure 0007634096000002
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of Chinese patent application No. 202010820725.0, filed on August 14, 2020, the contents of which are incorporated herein by reference.
[0002] Technical Field The present invention relates to polymers suitable for oil well cements, oil well cement dispersants, methods for their preparation and use. [Background technology]
[0003] Cementing is an essential process in oil exploration and development, which requires pumping cement slurry into the annular space between the casing and the shaft. In order to meet the requirements of high cementing quality and the cementing construction situation where various types of oil well cements appear one after another, adding various additives to the cement slurry to adjust the overall performance of the cement slurry has become the key technology of cementing.
[0004] Conventional cement additives include water loss inhibitors, setting regulators (setting retarders, setting accelerators), dispersants, density reducers, and density enhancers. Water loss inhibitors reduce the amount of water lost from the cement slurry and prevent dehydration of the cement slurry. Setting retarders and setting accelerators are used to adjust the setting time of the cement slurry, and some setting accelerators increase the initial strength of the hardened cement body. The addition of these additives often reduces the fluidity of the slurry, making pumping difficult. For this reason, it is necessary to add a dispersant to improve the fluidity of the cement slurry.
[0005] Sulfonated ketone aldehyde polycondensate dispersants are dispersant products developed in the early 1990s, and are currently one of the most widely used dispersants in oil well cement both at home and abroad in China. Such dispersants have a wide range of raw material sources, reasonable prices, and better high temperature resistance than naphthalene-based products, making them suitable for many oil well cements. However, as exploration and development progress and environmental protection requirements become increasingly strict, the shortcomings of sulfonated aldehyde ketone polycondensate dispersants have also become apparent. 1) Due to the toxicity and polluting nature of the raw materials, production and use are unfriendly to the environment, and the toxicity and side effects are great. 2) The dispersing ability is low and the mixing amount is large. 3) Although silica fume, latex, etc. are mixed into the complex system, the dispersing ability is insufficient. 4) The compatibility with other new additives is poor.
[0006] The dispersants commonly used in the construction industry are polycarboxylic acid dispersants. Usually, such polycarboxylic acid dispersants are formed by radical polymerization of unsaturated acid monomers such as acrylic acid, maleic acid, itaconic acid, etc., and polyether macromonomers such as methacrylic alcohol polyoxyethylene / polyoxypropylene ether, isopentenol polyoxyethylene ether, etc., and have a comb-shaped molecular structure. Such dispersants can be used in various cement slurry systems by changing the acid-ether ratio, side chain length, density, etc., and have good dispersing effect. However, research has revealed that polycarboxylic acid dispersants for construction are weak at high temperatures and are easily decomposed above 70 ° C, which causes the setting of cement slurry to be delayed and even super-delayed, so that the direct application of this polycarboxylic acid dispersant to oil well cement cannot meet the needs of cementing. Polycarboxylic acid dispersants have a dispersing effect due to the electrostatic repulsion of the carboxylic acid groups in the molecular structure, which adsorb to the surface of cement particles. Therefore, generally, the higher the acid-ether ratio in the molecular structure (i.e., the higher the carboxylic acid content), the higher the adsorption performance and dispersing effect. However, this significantly inhibits the hydration of cement, and especially in cementing work at medium and low temperatures of 30 to 120°C, there are problems such as long setting time, low early strength, and setting delay or super setting delay. Furthermore, such conventional polycarboxylic acid dispersants have low dispersing effect and problems such as compatibility when used in combination with water loss inhibitors and setting retarders commonly used in oil well cement. Summary of the Invention [Problem to be solved by the invention]
[0007] Since the construction technology of cementing construction has the characteristics of many additives and admixtures, the requirements for oil well cement dispersants for cementing are more than those for building cement, and there are mainly three: 1. High dispersibility, such as high density cement slurry, low density cement slurry, latex cement slurry, liquid silicon cement slurry, etc., which have good dispersing effect on special cement slurry systems other than ordinary cement slurries. 2. Do not delay the hydration of cement and do not affect early strength, that is, setting delay is disadvantageous to oil well cement dispersants, which increases the risk of gas channeling during the hardening of cement slurry, affecting the setting of the low temperature part of the cement ring, prolonging the setting time, affecting the construction period, and in serious cases, causing construction accidents with super setting delay; on the other hand, adding setting accelerators and early strength agents to polycarboxylic acid-based dispersants tends to have insufficient setting effect due to the strong adsorption action of polycarboxylic acid, and also brings risks to construction. 3. Blending with many types of additives: Many of the current polycarboxylic acids have compatibility problems with other oil well cement additives, especially new polymer-based setting retarders and water loss inhibitors. Problems such as inability to suppress water loss and inability of dispersants to function exist, and these problems need to be resolved as soon as possible.
[0008] Regarding the current problems and technical difficulties of oil well cement dispersants, the inventors have introduced a large amount of sulfonic acid instead of part of the carboxylic acid, and the sulfonic acid plays the main adsorption role, thereby ensuring high dispersibility due to the steric hindrance of the comb-like structure of the polymer, while eliminating the retardation caused by the carboxylic acid group, and effectively shortening the setting time; and by introducing long-chain silane into the polymer, the dispersant realizes a chemical anchoring action through the condensation action of the silyl group with the cement particles and the surface of the hydration product, thereby enhancing the adsorption action of the dispersant on the surface of the cement-based material particles; unlike the case of using conventional polycarboxylic acid dispersants in combination with other additives (e.g., setting retarders, water loss inhibitors), these additives also have charge adsorption groups such as carboxylic acid and sulfonic acid, so that competitive adsorption occurs and the failure of the dispersant is avoided; the compatibility of the dispersant with other additives is improved; on the other hand, the hydrophobicity of the long-chain group destroys the thick hydration film formed on the surface of the cement particles along the comb-like structure of the polyether segment in the dispersant, destroying the setting retardation brought about by the hydration film, and thus obtaining the effect of reducing the setting retardation. In addition, in a preferred embodiment, by using sulfonic acid having a benzene ring, the hydrophobic effect of the benzene ring and the hydrophobic effect of the long-chain silane can exert a synergistic effect, and when the dispersant is adsorbed on the surface of the cement particle, a hydrophobic region is generated in the thick hydration film formed along the comb tooth direction of the comb polymer, and the integrity of the hydration film structure is destroyed from the inside, which helps to destroy the hydration film, thereby further reducing the setting retardation caused by the thick hydration film and improving the early strength of the cement. Therefore, unlike conventional dispersants, this dispersant has the high dispersibility of polycarboxylic acid comb dispersants, and at the same time solves the side effect of its setting retardation from the mechanism angle, which is extremely important for cementing work, and ensures the rheological performance of the cement slurry while ensuring its timely setting, which is favorable for preventing leakage and channeling, and shortens the construction period while ensuring safe construction. This has led to the completion of the present invention. The polymer and cement dispersant according to the present invention have good dispersing effect, short setting time and high early strength, and are particularly suitable for use in low- to medium-temperature cementing work at 30°C to 120°C. [Means for solving the problem]
[0009] The first aspect of the present invention is A polymer having dispersing properties, Contains structural units a, b, c, and d, The structural unit a is derived from an unsaturated polyether and / or polyester, the structural unit b is derived from an unsaturated carboxylic acid and / or an acid anhydride thereof and / or a salt thereof, the structural unit c is derived from a silane and / or siloxane containing a polymerizable group, the structural unit d is derived from an unsaturated sulfonic acid and / or a salt thereof, the molar ratio of the structural unit a to the structural unit d is 1:(5 to 15), preferably 1:(6 to 10), and the weight average molecular weight of the polymer is 20,000 to 120,000.
[0010] According to some embodiments of the present invention, the molar ratio of structural unit a:structural unit b:structural unit c is 1:(0.5-6):(0.01-4), preferably 1:(1-4):(0.05-2), and more preferably 1:(1-4):(0.1-1).
[0011] According to some embodiments of the present invention, the molar ratio of the structural unit b to the structural unit d is 1:(2-8).
[0012] According to some embodiments of the invention, the unsaturated polyester has a structure represented by formula (I): The unsaturated polyether has a structure represented by formula (II). [ka] (In formula (I), A represents an alkylene group having 2 to 4 carbon atoms; B represents an alkylene group having 2 to 4 carbon atoms other than A; R 1 and R 2 each independently represents H or an alkyl group having 1 to 5 carbon atoms, preferably a methyl group; R 3 represents an alkyl group having 1 to 4 carbon atoms, X represents an alkylene group having 1 to 5 carbon atoms; m represents an integer of 0 to 200, preferably 20 to 140; n represents an integer of 0 to 200, preferably 20 to 140; m+n>10, preferably m+n≧40. [ka] (In formula (II), E represents an alkylene group having 2 to 4 carbon atoms; F represents an alkylene group having 2 to 4 carbon atoms other than E; R 4 and R 5 each independently represents H or an alkyl group having 1 to 5 carbon atoms, preferably a methyl group; R 6 represents an alkyl group having 1 to 4 carbon atoms, Y represents an alkylene group having 1 to 5 carbon atoms; p represents an integer of 0 to 200, preferably 20 to 140; q represents an integer of 0 to 200, preferably 20 to 140; p+q>10, preferably p+q≧40.
[0013] In the present invention, the term "unsaturated acid and / or its salt and / or its acid anhydride" refers to one or more of an unsaturated acid, a sodium salt, a potassium salt, an ammonium salt of an unsaturated acid, and an acid anhydride of an unsaturated acid.
[0014] According to some embodiments of the present invention, the unsaturated carboxylic acid has a structure represented by formula (1): [ka] In formula (1), R1, R2, and R3 are each independently selected from hydrogen, a C1-C6 alkyl group, and -COOH, and X is (CH2) n and n is 0, 1, 2, 3, 4, 5, or 6.
[0015] According to some embodiments of the present invention, the unsaturated carboxylic acid and / or its anhydride and / or its salt is one or more selected from acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid, and their anhydrides or salts thereof.
[0016] According to some embodiments of the present invention, the unsaturated sulfonic acid and / or its salt contains a substituted or unsubstituted benzene ring or amide group, and preferably, the unsaturated sulfonic acid or its salt has a structure represented by any one of formulas (IIIA) to (IIID). [ka] (In formula IIIA, formula IIIB and formula IIIC, R1, R2, R3 and R4 are each independently selected from hydrogen, halogen, a C1-C6 alkyl group and a C1-C6 alkoxy group, and X is (CH2) n where n is an integer from 0 to 6, and M is hydrogen or a metal ion, for example an alkali metal ion, preferably a lithium ion, a sodium ion, or a potassium ion; In formula IIID, R1, R2, and R3 are each independently selected from hydrogen and a C1-C6 alkyl group, and X is (CH2) n where n is an integer of 0 to 6, and M is hydrogen or a metal ion, for example an alkali metal ion, preferably a lithium ion, a sodium ion, or a potassium ion.
[0017] According to some embodiments of the present invention, the unsaturated sulfonic acid or salt thereof is one or more selected from 2-acrylamido-2-methylpropanesulfonic acid, 2-acrylamido-2-methylpropanesulfonate, p-styrenesulfonic acid, p-styrenesulfonate, methyl p-styrenesulfonate, p-styrenesulfonate, allylsulfonic acid, and allylsulfonate.
[0018] In the present invention, the polymerizable group may be one or more of various groups that can undergo a bonding reaction with other monomers under desired conditions, such as a carbon-carbon double bond, a carbon-carbon triple bond, and an epoxy group.
[0019] The silane and / or siloxane used in the present invention is preferably a silane and / or siloxane having a linear carbon number between the silicon atom and the polymerizable group of 5 or more, preferably 7 or more, more preferably 8 to 25, and even more preferably 8 to 18, where n may be 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, or 25.
[0020] Preferably, according to some embodiments of the present invention, the silane and / or siloxane has a structure represented by formula (IV): [ka] In formula (IV), R1, R2, R3, R1', and R2' are each independently selected from H and an alkyl group having C1 to C4; R a , R b and R c are each independently selected from H, a C1 to C4 alkyl group or an alkoxy group, and n is an integer of 5 to 25, preferably an integer of 8 to 18.
[0021] In the present invention, the number of carbon atoms in the linear chain between the polymerizable group and the silicon atom means the number of carbon atoms in the backbone carbon chain between the polymerizable group and the silicon atom, and n in the above formula (IV) is the number of carbon atoms in the linear chain between the polymerizable group and the silicon atom.
[0022] In the present invention, the C1-C4 alkyl group may be a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, or a t-butyl group.
[0023] In the present invention, the C1-C4 alkoxy group may be a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, an isobutoxy group, or a t-butoxy group.
[0024] The silane and / or siloxane used in the present invention may be, for example, vinyloctadecyltrimethoxysilane (i.e., in formula (I), n is 18, same as below), vinylhexadecyltrimethoxysilane, vinyltetradecyltrimethoxysilane, vinyldodecyltrimethoxysilane, vinyldecyldimethoxysilane, vinyloctyldimethoxysilane, 7-octenyltrimethoxysilane, vinylhexyldimethoxysilane, vinyloctadecyldimethoxysilane, vinylhexadecyldimethoxysilane, vinyltetradecyldimethoxysilane, vinyldodecyldimeth- xylsilane, vinyldecyldimethoxysilane, vinyloctyldimethoxysilane, vinylhexyldimethoxysilane, vinyloctadecyltrimethylsilane, vinylhexadecyltrimethylsilane, vinyltetradecyltrimethylsilane, vinyldodecyltrimethylsilane, vinyldecyltrimethylsilane, vinyloctyltrimethylsilane, vinylhexyltrimethylsilane, vinyloctadecyldimethylsilane, vinylhexadecyldimethylsilane, vinyltetradecyldimethylsilane, vinyldodecyldimethylsilane, vinyldecyldimethylsilane, Vinyl octyl dimethyl silane, vinyl hexyl dimethyl silane, propenyl octadecyl trimethoxy silane, propenyl hexadecyl trimethoxy silane, propenyl tetradecyl trimethoxy silane, propenyl dodecyl trimethoxy silane, propenyl decyl dimethoxy silane, propenyl octyl dimethoxy silane, propenyl hexyl dimethoxy silane, propenyl octadecyl dimethoxy silane, propenyl hexadecyl dimethoxy silane, propenyl tetradecyl dimethoxy silane, propenyl dodecyl dimethoxy silane, propenyl decyl ldimethoxysilane, propenyl octyl dimethoxysilane, propenyl hexyl dimethoxysilane, propenyl octadecyl trimethylsilane, propenyl hexadecyl trimethylsilane, propenyl tetradecyl trimethylsilane, propenyl dodecyl trimethylsilane, propenyl decyl trimethylsilane, propenyl octyl trimethylsilane, propenyl hexyl trimethylsilane, propenyl octadecyl dimethylsilane, propenyl hexadecyl dimethylsilane, propenyl tetradecyl dimethylsilane, propenyl dodecyl dimethylsilane,The silane may be one or more of propenyldecyldimethylsilane, propenyloctyldimethylsilane, and propenylhexyldimethylsilane.
[0025] In the present invention, the silane and / or siloxane (particularly long-chain silane) containing the polymerizable group may be commercially available or may be produced by a conventional method in this field. For example, first, a Grignard reagent having a structure represented by formula (IV') is reacted with tetrachlorosilane to obtain a long-chain chlorosilane, and then the obtained long-chain chlorosilane is alcoholyzed to obtain the silane coupling agent of the present invention. Here, the production conditions of the silane coupling agent are not particularly limited, and it is sufficient to satisfy the needs of the present invention. [ka] In formula (IV'), R1, R2, R3, R1', R2', R a , R b , R c and n are the same as those in formula (IV). Alternatively, a long-chain chlorosilane is reacted with a Grignard reagent, and a coupling action is performed between the Grignard reagent (Grignard reagent is also called Grignard reagent, and is a hydrocarbon group magnesium halide (R-MgX)) and an alkyl halide to produce a hydrocarbon. For example, vinylheptadecyldimethylsilane can be obtained by reacting hexadecyldimethylchlorosilane with allylmagnesium chloride, and the reaction formula is as follows: Cl(CH2) 16 SiH(CH3)2+H2C=CH-CH2MgCl→H2C=CH-CH2-(CH2) 16 SiH(CH3)2+MgCl2
[0026] The specific reaction conditions are well known to those skilled in the art and will not be described in detail herein. Unless otherwise specified, the silanes / siloxanes in the following examples of the present invention are prepared by the above methods.
[0027] In the present invention, the presence and molar contents of the structural units a, b, c and d are determined by infrared spectroscopy. 1 It can be measured by a method combining with 1 H-NMR.
[0028] According to some embodiments of the present invention, the polymer has a comb-like structure, which is a structure in which carbon-carbon double bonds are polymerized to form a backbone structure, and each structural unit is linked to a carbon-carbon double bond to form a pendant structure resembling the teeth of a comb.
[0029] According to some embodiments of the present invention, the polymer is a random copolymer. The fact that the polymer of the present invention is a random copolymer can be confirmed by a single peak in the DSC of the polymer.
[0030] A second aspect of the present invention provides a method for producing a dispersant, comprising a step of polymerizing a monomer mixture in water in the presence of an initiator under solution polymerization conditions, the monomer mixture containing monomer A, monomer B, monomer C, and monomer D, the monomer A being an unsaturated polyether and / or polyester, the monomer B being an unsaturated carboxylic acid and / or an acid anhydride thereof and / or a salt thereof, the monomer C being a silane and / or siloxane containing a polymerizable group, the monomer D being an unsaturated sulfonic acid and / or a salt thereof, the molar ratio of monomer A:monomer B:monomer C:monomer D being 1:(0.5-6):(0.01-4):(5-15), preferably 1:(1-4):(0.1-1):(6-10), and the polymerization conditions being such that the weight average molecular weight of the obtained polymer is 20,000 to 120,000.
[0031] According to some embodiments of the present invention, the polymerization reaction conditions include a temperature of 50-80° C., preferably 60-70° C., and a time of 2-10 hours, preferably 3-5 hours.
[0032] According to some preferred embodiments of the present invention, prior to the polymerization reaction, the monomer mixture is pre-oxidized, and the pre-oxidation is carried out in the presence of hydrogen peroxide (oxydol). Preferably, the amount of hydrogen peroxide used is 0.1-1 g per 60 g of monomer A. The hydrogen peroxide is preferably present in the form of a solution having a solute mass percentage of 20-40 wt %. The pre-oxidation time is 5-30 minutes.
[0033] According to some embodiments of the present invention, the initiator is at least one selected from oxydol-ascorbic acid (oxidizing agent-reducing agent), oxydol-vitamin C, sodium hydrogen sulfite, sodium formaldehyde sulfoxylate, and sodium dithionite, and the oxidizing agent is at least one selected from oxydol, peracetic acid, ammonium persulfate, sodium persulfate, and potassium persulfate. Preferably, the concentration of the oxydol is 25 to 35% by weight.
[0034] Preferably, the initiator is selected from oxydol-vitamin C and / or sodium bisulfite.
[0035] According to some embodiments of the present invention, the polymerization reaction is carried out in the presence of a chain transfer agent.
[0036] Preferably, the chain transfer agent is at least one selected from mercaptopropionic acid, thioglycolic acid, alkyl mercaptans, and isopropyl alcohol.
[0037] The amount of the solvent used is preferably such that the solid content of the product obtained by polymerization (the dispersant) is 15 to 50% by weight.
[0038] According to some embodiments of the invention, the method further comprises: (1) pre-oxidizing the monomer A at 50 to 70° C. to obtain a pre-oxidized material; (2) performing a first mixture of water with monomer B, monomer C, and monomer D to obtain a first mixture; (3) second mixing the water with the chain transfer agent and the initiator to obtain a second mixture; (4) adding the first mixture and the second mixture to the pre-oxidized material in step (1) to carry out a polymerization reaction.
[0039] In the present invention, in step (1), the preliminary oxidation is carried out in the presence of water, and the amount of water used is 50 to 110 g per 60 g of monomer A.
[0040] In the present invention, the pre-oxidation is carried out in the presence of hydrogen peroxide, and the amount of hydrogen peroxide used is 0.1 to 1 g per 60 g of monomer A. The hydrogen peroxide is preferably present in the form of a solution having a solute mass percentage of 20 to 40% by weight. The pre-oxidation time is 5 to 30 minutes.
[0041] In the present invention, the amount (weight) of water used in step (2) is 2 to 3.5 times the total amount (weight) of monomer B, monomer C, and monomer D used.
[0042] In step (3), the amount (weight) of water used is 50 to 150 times the total amount (weight) of the chain transfer agent and the initiator used.
[0043] In step (4), in order to prevent self-polymerization and explosive polymerization and make the comb-like structure more uniform and regular, the first mixture and the second mixture are preferably added to the material after pre-oxidation in step (1) in a simultaneous dropwise manner. When the dropwise manner is adopted, the above polymerization reaction time includes the dropwise time, that is, the polymerization reaction time is calculated from the start of the dropwise addition. Preferably, in order to carry out the polymerization more thoroughly, the warming reaction is continued for 0.5 to 1.5 hours after the dropwise addition of the material is completed.
[0044] In the present invention, after the polymerization reaction, the polymerized material (containing solvent) can be directly used as a cement slurry dispersant without further post-treatment, however, when characterizing the related structures, the polymer may be subjected to corresponding purification treatment according to the characterization requirements.
[0045] In the present invention, the content of each monomer structure in the polymer and the structural characteristics of the polymer may be measured by conventional methods in the prior art, and the characterization is carried out, for example, by infrared spectroscopy, nuclear magnetism, gel chromatography, TGA-DSC, etc. Specifically, for example, in infrared spectroscopy, -1 The absorption peak at 3442 cm corresponds to the -OH of unsaturated acids. -1 and 1110cm -1 The absorption peak at 30-30 cm corresponds to -OH and -COC- of unsaturated polyether monomers (e.g., TPEG), -1 corresponds to =CH of the benzene ring, and 1650 cm -1 ~1450cm -1 and 900cm -1 ~650cm -1 The multiple absorption peaks in the benzene ring all correspond to 1593 cm -1 corresponds to -COO- of unsaturated acids (e.g. acrylic acid), and 1461cm -1 and 2882 cm -1 corresponds to CH2 in the long chain of long linear silanes and / or siloxanes, and 1347 cm -1 corresponds to -Si-C-, and 1100 cm -1 corresponds to -CO- or -Si-O-, and 1190cm -1 , 1068cm -1 , 620cm -1 , 530cm -1 The absorption peak at 1660 cm corresponds to the sulfonic acid group, and the C-C double bond in styrene corresponds to 1660 cm -1 Since the double bond is opened, this peak does not have a characteristic absorption peak. Similarly, -1 The absence of an absorption peak between indicates that there is no remaining olefin "-C=C-".
[0046] The molecular weight and distribution of the polymer are measured by gel permeation chromatography (GPC).
[0047] The polymerization product obtained by the above method can be used as it is as a cement dispersant without requiring a separation and purification step.
[0048] A third aspect of the present invention provides a cement composition comprising the above-mentioned dispersant and cement, and preferably, the content of the dispersant is 0.05 to 5 wt %, preferably 0.1 to 1 wt %, based on the total amount of the cement composition.
[0049] In the present invention, the content of the dispersant includes the amount of the solvent in the dispersant.
[0050] According to some embodiments of the present invention, the composition further comprises a water loss prevention agent, preferably, the water loss prevention agent is one or more selected from cellulose-based, polyvinyl alcohol-based and AMPS-based water loss prevention agents, more preferably, the water loss prevention agent is selected from AMPS-based water loss prevention agents.
[0051] The amount of the water leakage prevention agent used is generally 1 to 10% by weight of the total amount of the cement composition.
[0052] A fourth aspect of the present invention provides use of the above polymer, the above dispersant or the above cement composition in oil well cement or oil well construction, preferably the oil well construction is carried out at 20°C to 120°C.
[0053] The polymer of the present invention is used as an oil well cement dispersant, which can eliminate the strong hydration inhibition effect of general dispersants at 20 to 120 ° C., reduce the content of carboxyl groups, and increase the sulfonic acid groups, thereby reducing the hydration inhibition effect and reducing the setting retardation. In addition, since the long-chain silane is linked to the cement and hydration products through chemical bonds, the adsorption is improved, and it can be effectively adjusted by mixing with sulfonic acid without affecting the dispersibility of the cement setting retardation. In use, the dispersant not only solves the problem of the flow performance of the cement slurry, but also improves the settling stability of the slurry, and is well compatible with additives, and has good compatibility and dispersibility with admixtures such as microsilica and latex, and can be applied to the step of medium and low temperature cementing, meeting the practical needs of oil well cement dispersants. [Brief description of the drawings]
[0054] [Figure 1] FIG. 2 is a gel chromatography analysis diagram of the polymer produced in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0055] The present invention will now be described in detail with reference to examples, but the present invention is not limited to the following examples.
[0056] Raw materials used in the examples and comparative examples are either commercially available or prepared by conventional methods, unless otherwise specified.
[0057] In the following examples and comparative examples, the content of each structural unit in the polymer is determined by the amount of monomer input, specifically, the input ratio of each monomer actually involved in polymerization is determined by measuring the content of unreacted monomer, and the content of each structural unit in the polymer is determined, and the solid content is calculated from the input amount, that is, solid content = input amount excluding solvent (weight) / input amount including solvent (weight) * 100%.In the examples, since only a single peak appears in the DSC spectrum of the polymer, it is clear that all the polymers are random copolymers.
[0058] Example 1 101g of water and 60g (0.025mol) of isopentenol polyoxyethylene ether (TPEG, weight average molecular weight 2400) were weighed, uniformly dissolved and mixed, and placed in a three-necked flask in a thermostatic water bath pot, stirred at a constant speed of 200 rpm with a stirring blade, heated to 65°C, and 0.52g of H2O2 with a mass concentration of 30% was weighed and added to the three-necked flask. 3.6g of acrylic acid (AA), 36.8g of p-styrenesulfonic acid, 3g of vinyloctadecyltrimethoxysilane, and 100g of water were uniformly mixed to prepare dripping solution A, and 0.48g of mercaptopropionic acid, 0.21g of vitamin C, and 45g of water were uniformly mixed to prepare dripping solution B. Droplet A and Droplet B were added dropwise at equal speeds to a three-neck flask using a peristaltic pump, with the drop time for Droplet A being 3 hours and Droplet B being 3.5 hours. After the drop was completed, the mixture was kept warm for 1 hour. The actual solid content of the obtained sample was 30.0% by weight. As a result of gel chromatography analysis (Figure 1), the weight average molecular weight of the polymer was 50280.
[0059] Example 2 98g of water and 60g (0.025mol) of isopentenol polyoxyethylene ether (TPEG, weight average molecular weight 2400) were weighed, uniformly dissolved and mixed, and placed in a three-necked flask in a thermostatic water bath pot, stirred at a constant speed of 200 rpm with a stirring blade, heated to 65°C, and 0.52g of H2O2 with a mass concentration of 30% was weighed and added to the three-necked flask. 7.2g of acrylic acid (AA), 27.6g of p-styrenesulfonic acid, 5.81g of 7-octenyltrimethoxysilane, and 100g of water were uniformly mixed to prepare dripping solution A, and 0.48g of mercaptopropionic acid, 0.21g of vitamin C, and 45g of water were uniformly mixed to prepare dripping solution B. Dropping solution A and dropping solution B were dropped at equal speed into a three-neck flask using a peristaltic pump, and the dropping time of dropping solution A was 3 hours, and the dropping time of dropping solution B was 3.5 hours. After the dropping was completed, the mixture was kept warm for 1 hour. The actual solid content of the obtained sample was 30.1% by weight. The weight average molecular weight of the polymer was 52,000.
[0060] Example 3 103g of water and 60g (0.025mol) of isopentenol polyoxyethylene ether (TPEG, weight average molecular weight 2400) were weighed, uniformly dissolved and mixed, and placed in a three-necked flask in a thermostatic water bath pot, stirred at a constant speed of 200 rpm with a stirring blade, heated to 65°C, and 0.52g of H2O2 with a mass concentration of 30% was weighed and added to the three-necked flask. 3.25g of itaconic acid (IA), 46g of p-styrenesulfonic acid, 3.95g of vinyldodecyltrimethoxysilane, and 100g of water were uniformly mixed to prepare dripping solution A, and 0.55g of mercaptopropionic acid, 0.24g of vitamin C, and 65g of water were uniformly mixed to prepare dripping solution B. Dropping solution A and dropping solution B were dropped at equal speed into a three-neck flask using a peristaltic pump, and the dropping time of dropping solution A was 3 hours, and the dropping time of dropping solution B was 3.5 hours. After the dropping was completed, the mixture was kept warm for 1 hour. The actual solid content of the obtained sample was 29.9% by weight. The weight average molecular weight of the polymer was 53,890.
[0061] Example 4 A polymerization reaction was carried out in the same manner as in Example 1, except that 36.8 g of p-styrenesulfonic acid was replaced by the same molar amount of 41.4 g of 2-acrylamide-2propanesulfonic acid (AMPS). The actual solid content of the obtained sample was 29.7% by weight, and the weight average molecular weight of the polymer was 54,130.
[0062] Example 5 Except for changing 3 g of vinyloctadecyltrimethoxysilane to the same molar amount of 1.86 g of γ-methacryloyloxypropyltrimethoxysilane, the polymerization reaction was carried out in the same manner as in Example 1. The actual solid content of the obtained sample was 30.2 wt %, and the weight average molecular weight of the polymer was 51,768.
[0063] Example 6 A polymerization reaction was carried out in the same manner as in Example 1, except that 36.8 g of p-styrenesulfonic acid was replaced by the same molar amount of 2-acrylamido-2propanesulfonic acid (AMPS), and 3 g of vinyloctadecyltrimethoxysilane was replaced by the same molar amount of γ-methacryloyloxypropyltrimethoxysilane. The actual solid content of the obtained sample was 30.1% by weight, and the weight average molecular weight of the polymer was 50,354.
[0064] Example 7 The polymerization reaction was carried out in the same manner as in Example 1, except that the molar ratio of TPEG:acrylic acid (AA):sulfonic acid was 1:5:5. The polymerization reaction was carried out in the same manner as in Example 1. The actual solid content of the obtained sample was 29.8 wt %, and the weight average molecular weight of the polymer was 50211.
[0065] Example 8 70g of water and 60g of HPEG were weighed, uniformly dissolved and mixed, and placed in a three-necked flask in a thermostatic water bath pot. The mixture was stirred at a constant speed of 200 rpm with a stirring blade, heated to 65°C, and 0.52g of H2O2 with a mass concentration of 30% was weighed and added to the three-necked flask. 3.6g of AA, 31.1g of AMPS, 0.62g of KH570, and 100g of water were uniformly mixed to prepare dripping solution A, and 0.48g of mercaptopropionic acid, 0.21g of vitamin C, and 45g of water were uniformly mixed to prepare dripping solution B. Dripping solution A and dripping solution B were dripped into the three-necked flask at a constant speed using a peristaltic pump, and the dripping time of dripping solution A was 3h, and the dripping time of dripping solution B was 3.5h. After dripping was completed, the mixture was kept warm for 1h. The actual solid content was 30.2 wt % and the weight average molecular weight of the polymer was 51,070.
[0066] Example 9 70g of water and 60g of TPEG were weighed, uniformly dissolved and mixed, and placed in a three-necked flask in a thermostatic water bath pot. The mixture was stirred at a constant speed of 200 rpm with a stirring blade, heated to 65°C, and 0.58g of H2O2 with a mass concentration of 30% was weighed and added to the three-necked flask. 9.76g of IA, 31.1g of AMPS, 1.24g of KH570, and 100g of water were uniformly mixed to prepare dripping solution A, and 0.54g of mercaptopropionic acid, 0.23g of vitamin C, and 60g of water were uniformly mixed to prepare dripping solution B. Dripping solution A and dripping solution B were dripped into the three-necked flask at a constant speed by a peristaltic pump, and the dripping time of dripping solution A was 3.5h, and the dripping time of dripping solution B was 4h. After dripping was completed, the mixture was kept warm for 1.5h. The actual solid content was 30.3 wt % and the weight average molecular weight of the polymer was 50,911.
[0067] Comparative Example 1 Except for changing 36.8 g of p-styrenesulfonic acid to the same molar amount of 14.4 g of acrylic acid (AA), a polymerization reaction was carried out in the same manner as in Example 1. The actual solid content of the obtained sample was 29.5 wt %, and the weight average molecular weight of the polymer was 43,627.
[0068] Comparative Example 2 Except for not adding vinyloctadecyltrimethoxysilane, a polymerization reaction was carried out in the same manner as in Comparative Example 1. The actual solid content of the obtained sample was 29.9% by weight, and the weight average molecular weight of the polymer was 51,397.
[0069] Comparative Example 3 The polymerization reaction was carried out in the same manner as in Example 15 of CN108250370A. The actual solid content of the obtained sample was 29.6 wt%, and the weight average molecular weight of the polymer was 50280.
[0070] Comparative Example 4 Except for not adding TPEG, AA, and vinyloctadecyltrimethoxysilane, the polymerization reaction was carried out in the same manner as in Example 1. The actual solid content of the obtained sample was 29.1% by weight, and the weight average molecular weight of the obtained polymer was 71,583.
[0071] Performance measurement: (1) Cement slurry was produced according to the GB / T 19139-2003 standard, and the rheological properties and setting time were evaluated. The cement used was G-grade cement manufactured by Sichuan Jiahua Co., Ltd., the composition of paste 1 was 100 parts by weight of cement + 40 parts by weight of water, and the amount of dispersant (mixture obtained by polymerization) added in Comparative Examples 1 to 4 and Examples 1 to 7 accounted for 0.4% of the mass of cement. The detection results are shown in Table 1.
[0072] [Table 1]
[0073] As can be seen from Table 1, the dispersant prepared according to the present invention has low set retardation while maintaining good dispersibility when the amount of sulfonic acid used is high.
[0074] (2) Cement slurry was prepared according to GB / T 19139-2003 standard, and the rheological properties, setting time, and compressive strength were evaluated. The composition of Paste 2 was 100 parts by weight of cement + 4 parts by weight of water loss inhibitor + 44 parts by weight of water, and the amount of dispersant added was 0.7% of the cement mass. The water loss inhibitor was SCF-180L water loss inhibitor manufactured by China Petroleum Engineering Research Institute, and the remainder was of the same origin as in Mixture 1. The detection results are shown in Table 2.
[0075] [Table 2]
[0076] As can be seen from Table 2, when mixed with a water loss inhibitor, the dispersant of the present invention has a remarkable dispersing effect, has little effect on the setting time, and does not reduce the compressive strength of the hardened cement body.
[0077] (3) Cement slurry was prepared according to GB / T 19139-2003 standard, and the rheological properties, setting time, and compressive strength were evaluated. The composition of paste 3 was 450g cement + 225g silicon powder + 225g manganese powder (density enhancer) + 31.5g water loss inhibitor + 27g nano liquid silicon + 27g latex + 14g set retarder + 2g dispersant + 200g on-site water. The water loss inhibitor was SCF-180L water loss inhibitor (AMPS-based water loss inhibitor) manufactured by China Petroleum Engineering Research Institute, the set retarder was SCR-3 set retarder (acid-based set retarder) manufactured by China Petroleum Engineering Research Institute, and the rest were of the same origin as in mix 1. The detection results are shown in Table 3.
[0078] [Table 3]
[0079] Mixture 3 is a commonly used cementing cement slurry mix. As can be seen from Table 3, the dispersant of the present invention has excellent compatibility with other auxiliary agents of the cement slurry, has a significant dispersion effect, has little effect on the setting time, and does not reduce the compressive strength of the hardened cement body. On the other hand, when Comparative Example 1 and Comparative Example 3 are used in combination with a retarder, the dispersibility of both is affected, the dispersing ability is lower than that of the dispersant of the present invention, and the setting retardation time is significantly longer.
[0080] Although the present invention has been described in detail, modifications within the spirit and scope of the present invention will be apparent to those skilled in the art. It should be noted that each aspect described in the present invention, each part of each specific embodiment, and each feature described can be combined or exchanged in whole or in part. In each of the above specific embodiments, it is understood by those skilled in the art that an embodiment referring to another specific embodiment may be appropriately combined with other embodiments. Furthermore, as can be understood by those skilled in the art, the above is merely an illustrative form, and does not limit the present invention.
Claims
1. A polymer having dispersing properties, Contains structural units a, b, c, and d, the structural unit a is derived from an unsaturated polyether and / or an ester compound having a structure represented by formula (I), the structural unit b is derived from an unsaturated carboxylic acid or an acid anhydride thereof or a salt thereof, the structural unit c is derived from a silane and / or a siloxane containing a polymerizable group, and the structural unit d is derived from an unsaturated sulfonic acid and / or a salt thereof, The molar ratio of the structural unit a to the structural unit d is 1:(5 to 15); The polymer has a weight average molecular weight of 20,000 to 120,000. 【Chemistry 1】 (In formula (I), A represents an alkylene group having 2 to 4 carbon atoms; B represents an alkylene group having 2 to 4 carbon atoms other than A; R 1 and R 2 each independently represents H or an alkyl group having 1 to 5 carbon atoms, R 3 represents an alkyl group having 1 to 4 carbon atoms, X represents an alkylene group having 1 to 5 carbon atoms; m is an integer from 0 to 200; n is an integer from 0 to 200, m+n>10.)
2. 2. The polymer according to claim 1, wherein the molar ratio of the structural unit a to the structural unit d is 1:(6 to 10).
3. 3. The polymer according to claim 1, wherein the molar ratio of the structural unit a: the structural unit b: the structural unit c is 1:(0.5-6):(0.01-4).
4. 4. The polymer according to claim 3, wherein the molar ratio of the structural unit a: the structural unit b: the structural unit c is 1:(1-4):(0.1-1).
5. The polymer according to any one of claims 1 to 4, wherein the unsaturated polyether has a structure represented by formula (II). 【Chemistry 2】 (In formula (II), E represents an alkylene group having 2 to 4 carbon atoms; F represents an alkylene group having 2 to 4 carbon atoms other than E; R 4 and R 5 each independently represents H or an alkyl group having 1 to 5 carbon atoms, R 6 represents an alkyl group having 1 to 4 carbon atoms, Y represents an alkylene group having 1 to 5 carbon atoms; p represents an integer of 0 to 200; q represents an integer of 0 to 200; p+q>10.)
6. In formula (I), R 1 and R 2 each independently represents a methyl group; m represents 20 to 140; n represents 20 to 140; m+n≧40; In formula (II), R 4 and R 5 each independently represents a methyl group; p represents 20 to 140; q represents 20 to 140; The polymer of claim 5 , wherein p+q≧40.
7. The polymer according to any one of claims 1 to 6, wherein the unsaturated carboxylic acid comprises one or more selected from the group consisting of acrylic acid, methacrylic acid, itaconic acid, fumaric acid and maleic acid.
8. The polymer according to any one of claims 1 to 7, wherein the unsaturated sulfonic acid or a salt thereof contains a substituted or unsubstituted benzene ring or an amide group.
9. The polymer according to claim 8, wherein the unsaturated sulfonic acid and / or salt thereof comprises a structure represented by any one of formulas (IIIA) to (IIID). 【Chemistry 3】 (In formula IIIA, formula IIIB and formula IIIC, R 1 , R 2 , R 3 and R 4 are each independently selected from hydrogen, halogen, a C1-C6 alkyl group, and a C1-C6 alkoxy group, and X is (CH 2 ) n where n is an integer from 0 to 6, and M is hydrogen or a metal ion; In formula IIID, R 1 , R 2 and R 3 are each independently selected from hydrogen and a C1-C6 alkyl group, and X is (CH 2 ) n where n is an integer from 0 to 6, and M is hydrogen or a metal ion.
10. 10. The polymer of claim 9, wherein in formula IIIA, IIIB and IIIC, M is an alkali metal ion, and in formula IIID, M is an alkali metal ion.
11. The polymer according to claim 9, wherein in formula IIIA, formula IIIB and formula IIIC, M is a lithium ion, a sodium ion or a potassium ion, and in formula IIID, M is a lithium ion, a sodium ion or a potassium ion.
12. The polymer according to claim 8, wherein the unsaturated sulfonic acid or a salt thereof is one or more selected from 2-acrylamido-2-methylpropanesulfonic acid, 2-acrylamido-2-methylpropanesulfonate, p-styrenesulfonic acid, p-styrenesulfonate, methyl p-styrenesulfonate, methyl p-styrenesulfonate, allylsulfonic acid, and allylsulfonate.
13. The polymer according to any one of claims 1 to 12, wherein the silane and / or siloxane containing a polymerizable group has 5 or more carbon atoms, and the polymerizable group is one or more of a carbon-carbon double bond, a carbon-carbon triple bond, and an epoxy group.
14. The polymer of claim 13 , wherein the silane and / or siloxane containing a polymerizable group has a structure represented by formula (IV). 【Chemistry 4】 (In formula (IV), R 1 , R 2 , R 3 , R 1 ', and R 2 Each ' is independently selected from H, a C1-C4 alkyl group, and R a , R b and R c are each independently selected from H, a C1-C4 alkyl group or an alkoxy group, and n is an integer from 5 to 25.
15. The polymer according to claim 13, wherein the silane and / or siloxane containing a polymerizable group is at least one of 7-octenyltrimethoxysilane, vinyloctadecyltrimethoxysilane, vinylhexadecyltrimethoxysilane, and vinyldodecyltrimethoxysilane.
16. 1. A method for producing a dispersant, comprising the steps of polymerizing a monomer mixture in water in the presence of an initiator under solution polymerization conditions, the monomer mixture contains monomer A, monomer B, monomer C, and monomer D, the monomer A is an unsaturated polyether and / or an ester compound having a structure represented by formula (I), the monomer B is an unsaturated carboxylic acid and / or an acid anhydride thereof and / or a salt thereof, the monomer C is a silane and / or a siloxane containing a polymerizable group, the monomer D is an unsaturated sulfonic acid and / or a salt thereof, the molar ratio of monomer A:monomer B:monomer C:monomer D is 1:(0.5-6):(0.01-4):(5-15), and the polymerization conditions are such that the weight average molecular weight of the obtained polymer is 20,000 to 120,000. 【Chemistry 5】 (In formula (I), A represents an alkylene group having 2 to 4 carbon atoms; B represents an alkylene group having 2 to 4 carbon atoms other than A; R 1 and R 2 each independently represents H or an alkyl group having 1 to 5 carbon atoms, R 3 represents an alkyl group having 1 to 4 carbon atoms, X represents an alkylene group having 1 to 5 carbon atoms; m is an integer from 0 to 200; n is an integer from 0 to 200, m+n>10.)
17. The method according to claim 16, wherein the molar ratio of monomer A:monomer B:monomer C:monomer D is 1:(1-4):(0.1-1):(6-10).
18. The unsaturated polyether has a structure represented by formula (II): And / or the method according to claim 16 or 17, wherein the unsaturated carboxylic acid comprises one or more selected from acrylic acid, methacrylic acid, itaconic acid, fumaric acid and maleic acid. 【Chemistry 6】 (In formula (II), E represents an alkylene group having 2 to 4 carbon atoms; F represents an alkylene group having 2 to 4 carbon atoms other than E; R 4 and R 5 each independently represents H or an alkyl group having 1 to 5 carbon atoms, R 6 represents an alkyl group having 1 to 4 carbon atoms, Y represents an alkylene group having 1 to 5 carbon atoms; p represents an integer of 0 to 200; q represents an integer of 0 to 200; p+q>10.)
19. In formula (I), R 1 and R 2 each independently represents a methyl group; m represents 20 to 140; n represents 20 to 140; m+n≧40; In formula (II), R 4 and R 5 each independently represents a methyl group; p represents 20 to 140; q represents 20 to 140; 20. The method of claim 18, wherein p+q>40.
20. The unsaturated sulfonic acid or its salt contains a substituted or unsubstituted benzene ring or an amide group. The method according to any one of claims 16 to 19.
21. The method according to claim 20, wherein the unsaturated sulfonic acid and / or salt thereof comprises a structure represented by any one of formulas (IIIA) to (IIID). 【Chemistry 7】 (In formula IIIA, formula IIIB and formula IIIC, R 1 , R 2 , R 3 and R 4 are each independently selected from hydrogen, halogen, a C1-C6 alkyl group, and a C1-C6 alkoxy group, and X is (CH 2 ) n where n is an integer from 0 to 6, and M is hydrogen or a metal ion; In formula IIID, R 1 , R 2 and R 3 are each independently selected from hydrogen and a C1-C6 alkyl group, and X is (CH 2 ) n where n is an integer from 0 to 6, and M is hydrogen or a metal ion.
22. 22. The method of claim 21, wherein in formula IIIA, IIIB and IIIC, M is an alkali metal ion, and in formula IIID, M is an alkali metal ion.
23. 23. The method of claim 22, wherein in Formula IIIA, Formula IIIB, and Formula IIIC, M is a lithium ion, a sodium ion, or a potassium ion, and in Formula IIID, M is a lithium ion, a sodium ion, or a potassium ion.
24. The method according to claim 20, wherein the unsaturated sulfonic acid or a salt thereof is one or more selected from 2-acrylamido-2-methylpropanesulfonic acid, 2-acrylamido-2-methylpropanesulfonate, p-styrenesulfonic acid, p-styrenesulfonate, methyl p-styrenesulfonate, methyl p-styrenesulfonate, allylsulfonic acid, and allylsulfonate.
25. The method according to any one of claims 16 to 24, wherein the silane and / or siloxane containing a polymerizable group has 5 or more carbon atoms, and the polymerizable group is one or more of a carbon-carbon double bond, a carbon-carbon triple bond, and an epoxy group.
26. 26. The method of claim 25, wherein the silane and / or siloxane containing a polymerizable group has a structure represented by formula (IV). 【Chemistry 8】 (In formula (IV), R 1 , R 2 , R 3 , R 1 ', and R 2 Each ' is independently selected from H, a C1-C4 alkyl group, and R a , R b and R c are each independently selected from H, a C1-C4 alkyl group or an alkoxy group, and n is an integer from 5 to 25.
27. 26. The method according to claim 25, wherein the silane and / or siloxane containing a polymerizable group is at least one of 7-octenyltrimethoxysilane, vinyloctadecyltrimethoxysilane, vinylhexadecyltrimethoxysilane, and vinyldodecyltrimethoxysilane.
28. 28. The method according to any one of claims 16 to 27, wherein the polymerization reaction is carried out in the presence of a chain transfer agent, and the polymerization reaction conditions include a temperature of 50 to 80°C and a time of 2 to 10 hours.
29. A cement composition comprising a cement and the polymer according to any one of claims 1 to 15 as a dispersant.
30. The cement composition according to claim 29, wherein the amount of the dispersant used is 0.05 to 5% by weight based on the total amount of the cement composition.
31. The cement composition according to claim 29 or 30, further comprising a water loss prevention agent, the water loss prevention agent being one or more selected from a cellulose-based water loss prevention agent, a polyvinyl alcohol-based water loss prevention agent, and an AMPS-based water loss prevention agent.
32. Use of the polymer according to any one of claims 1 to 15 or the cement composition according to any one of claims 29 to 31 in oil well cement or oil well construction.
Citation Information
Patent Citations
Silicon-containing polycarboxylate superplasticizer as well as preparation method and use thereof
CN104558434A
Silane polycarboxylate water-reducing agent and preparation method thereof
CN105837763A
Anti-mud water reducing agent for concrete and preparation method thereof
CN108840587A
Cement admixture
JP2000072505A
Use of polymers containing carboxyl groups and polyalkylene oxide ether-side chains as additives in mineral building materials
JP2001507054A